Study on Carcass Characteristics of Chicken Breeds Raised under the Intensive Condition - Musa, H.H.; Chen, G.H.; Cheng, J.H.; Li, B.C.; Mekki, D.M. (International Journal of Poultry Science, 2006)
Anka and Rugao chicken breed were reared under the same environment and management. During 12 weeks age the growth rate of Anka breed was found better than Rugao, and similarly within breeds Males were grow faster than females. The results shows that (live weight, carcass weight, dressing out percentage, semi-eviscerated weight, eviscerated weight, breast muscle weight, leg muscle weight, heart weight, liver weight and abdominal fat weight) were significantly (P< 0.01) different in Anka and Rugao breed, however the Abdominal fat % was statistically non significant (P>0.05) between breeds. Males compared to females shows significantly (P>0.01) higher live weight, carcass weight, semi-eviscerated weight, eviscerated weight, breast muscle weight, liver weight and abdominal fat weight within two breeds. However, Leg muscle weight, heart weight were non significantly different (P>0.05). In addition dressing out percentage was significantly (P< 0.05) different between males and females in Anka breed and non significantly in Rugao breed. In Anka chicken breed abdominal fat weight was positively correlated with live weight, carcass weight, breast muscle weight, and percentage of abdominal fat weight; and it was negatively correlated with leg weight. In Rugao breed abdominal fat weight was positively correlated with live weight, carcass weight, breast muscle weight, leg muscle weight and percentage of abdominal fat. However, the percentage of abdominal fat weight was negatively correlated with live weight, carcass weight, breast muscle weight and positively with leg muscle weight and abdominal fat weight.